Gambaran pengetahuan perilaku hidup bersih dan sehat siswa kelas VII di SMP Katolik Santa Theresia Manado - Lampus, Benny S.; Pandelaki, August J.; Grahandami, Grahandami (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
According to the vision that the future of the indonesian government about PHBS of indonesian who live in a healthy environment, the behavior of clean and healthy, able to reach health services, fair and equitable. The purpose of this research is to reveal the students knowledge of students of class VII at Catholic Junior High School Santa Theresia Manado about healthy behavior. This is descriptive study using a proportional approach. The sampling method used simple randam sampling with a sample of 55 people from a population of 120 people. The results obtained show that the knowledge of students of class VII at Catholic Junior High School Santa Theresia Manado is good, 100% of respondents knew how to wash their hands, and then 100% of respondents knew about healthy snacks, and by 87,3% of respondents knew about the use of latrines, then about 98,4% of respondents knew about the benefits of exercise, and approximately 96,3% of the respondents knew about the eradacation of mosquito larvae exercise, and thenÂ  approximately 96,3% respondents know about the dangers of smoking and about 80% respondents know about weighing and measuring height, and 100% of respondentsÂ  knew about the habit of taking out the trash. Keywords: Clean and Health Behaviour, Knowledge, Attitude and Behaviour